PENANGANAN CYBER ATTACKS OLEH PEMERINTAH TIONGKOK MELALUI KEBIJAKAN NETWORK SECURITY TAHUN 2000-2015 - Putri, Nadia Talita; Fasisaka, Idin; Nugraha, A.A.B. Surya Widya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 1 (2017), 2017)
ABSTRACT The development of Information and Communication Technology provide benefit and threat simultaneously for the countries that using it. China is one of the country that has been using Information and Communication Technology and China also claimed that the country has become world’s biggest victim of cyber attacks . Increasingly complexity of the problem in the security area, needed a respon to tackle cyber attacks and the Chinese government has a distinctive way to handle this problem. The research aims to describe the efforts to tackle cyber attacks by the Chinese government through the network security policy . This research using qualitative method and assessed by using concepts of network security and cyber security cooperation. The locus of this research is from 2000 until 2015. Key Word: China, network security, cyber security cooperation